The structure of service quality perceptions for multiple-encounter services - Andaleeb, Syed Saad; Kara, Ali (© 2013 Wolters Kluwer Health., 2016)
This article was published in the Quality Management in Health Care [©2013 Published by Wolters Kluwer Health] and the definite version is available at: http://doi.org/10.1097/QMH.0000000000000001 The Article's website is at: http://journals.lww.com/qmhcjournal/Abstract/2013/10000/The_Structure_of_Service_Quality_Perceptions_for.5.aspx